Haynes 242 Alloy for LARES 2 Satellite - D. Pilone; A. Brotzu; F. Felli; I. Ciufolini; B. Negri; C. Paris (Fracture and Structural Integrity)
The satellite LARES 2 is designed to test dragging of inertial frames, or frame-dragging, predicted by Einsteins theory of General Relativity, with accuracy of a few parts in a thousand. For this purpose, besides the typical requirements for a space construction, a high density alloy must be used. In this paper are reported the studies performed on a nickel alloy, the Haynes 242, that is considered a possible candidate for manufacturing all the metallic parts of LARES 2 and other passive geodetic satellites. Haynes 242 density and mechanical properties are compliant with the requirements of the mission. Three different casting with the nominal composition of the alloy have been prepared and tested along with a commercial bar of Haynes 242. The results of tensile and hardness tests on several specimens with different aging time are reported, along with the relevant metallographic analysis. Furthermore, a test on the machinability, performed on a screw, which is the most demanding item from the manufacturing point of view, is reported.